2021
DOI: 10.1086/711180
|View full text |Cite
|
Sign up to set email alerts
|

Contagious Animosity in the Field: Evidence from the Federal Criminal Justice System

Abstract: A vast literature uses ingroup biases to explain animus towards others. The notion can be extended to multi-identity societies, where social preferences are de…ned over one ingroup and multiple outgroups. We use a novel research design to recover the structure of social preferences across outgroups in a high stakes setting. We investigate whether increased animosity towards Muslims post 9-11 had spillover e¤ects on Black and Hispanic individuals in the federal criminal justice system. Using linked administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…This is outside the scope of our work in this paper. Such an explanation would be consistent withRasul and McConnell (2020) andSakong (2018).…”
supporting
confidence: 83%
“…This is outside the scope of our work in this paper. Such an explanation would be consistent withRasul and McConnell (2020) andSakong (2018).…”
supporting
confidence: 83%
“…19 The conditional gap that I document is larger than other papers in the literature. For instance, using a sample that is a subset of the one used here, McConnell and Rasul (2021) document an unconditional Blackwhite sentencing gap of a similar magnitude, but a conditional sentencing gap that is smaller by a factor of 3.…”
Section: Federal Cjsmentioning
confidence: 98%
“…Moreover, there is some evidence that negative press coverage of some out-groups, in this case EU immigrants, can also "spillover" into greater hostility toward other minorities. For example, US researchers have demonstrated that negative media portrayals linking Islamophobia and immigration following the 9/11 attacks (Romero and Zarrugh, 2018) resulted in longer prison sentences for minority group members perceived as immigrants (Rasul and McConnell, 2020). Analysis of a recent survey of mental health among migrants of all origins in the UK demonstrate how an increase in minority stress and social stigma, mediated via increased experiences of discrimination following the Referendum, resulted in worse mental health for both EU and non-EU migrants (Frost, 2020).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…There is also substantial evidence that media coverage of politicized events can heighten out-group hostility (Adena et al, 2015), reinforcing existing prejudices and even creating new ones (Gavin, 2018). The heightened salience of outgroup membership and increased hostility toward outgroup members which arises from significant events such as the September 11 terrorist attacks or the Trump campaign has further been shown to increase the prevalence of hate speech (Newman et al, 2020), actual acts of hate crime (Frey, 2020) and discriminatory practices toward ethnic minorities (Rasul and McConnell, 2020).…”
Section: Introductionmentioning
confidence: 99%